Assessment of Creative Thinking in Cultural Context in Junior High School Students - Indrani Eka Prastya Zahroh; Lathiful Anwar; Tjang Daniel Chandra (Universitas Suryakancana, 2025)
Creative thinking is an essential competence in mathematics learning because it enables students to generate diverse ideas, approach problems from multiple perspectives, and produce original solutions. However, in the Indonesian educational context, students’ creative thinking skills remain low, and current assessment tools have not adequately measured all dimensions of creativity namely fluency, flexibility, and originality. This study aims to fill this gap by developing and validating a culturally contextualized open-ended assessment instrument designed to measure students’ creative thinking skills comprehensively. Using a research and development (R&D) approach, the instrument was tested with 28 ninth grade students from a junior high school in Malang City. The instrument’s construct validity was examined through Exploratory Factor Analysis (EFA), and its internal consistency was tested using Cronbach’s Alpha. The findings indicate that the instrument demonstrates good reliability and a clear three factor structure aligning with theoretical dimensions of creative thinking. These results suggest that the developed assessment can effectively capture students’ creative potential within culturally relevant mathematical contexts. The study contributes to educational assessment practices by providing a valid and reliable tool that promotes culturally responsive approaches to fostering creative thinking in mathematics learning.